2019
DOI: 10.29252/hehp.7.3.111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of School-Based Mindfulness Training as a Program to Prevent Stress, Anxiety, and Depression in High School Students

Abstract: The effect of cognitive training on the ... [8] Evaluation of the correlations between depression ... [9] Effects of Mindfulness-Based Stress Reduction ... [10] Effectiveness of mindfulness-based stress reduction ... [11] Comparison of perfectionism, aggression and coping ... [12] Efficacy of family anxiety management training ... [13] The effectiveness of mindfulness-based stress reduction ... [14] Efficacy of mindfulness-based cognitive therapy ... [15] Effectiveness of teaching mindfulness techniques on ...… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A systematic review ( Erbe & Lohrmann, 2015 ) also reported that mindfulness is a highly effective school health intervention for the purpose of promoting stress relief, emotional regulation, and enhancing concentration in adolescents. Mostafazadeh et al (2019) reported that mindfulness training should be implemented in schools because they are effective in reducing depression, anxiety, and stress in high school students. Several other studies have reported that mindfulness programs are effective in lowering stress in children and adolescents ( Bluth et al, 2016 ; Kuyken et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review ( Erbe & Lohrmann, 2015 ) also reported that mindfulness is a highly effective school health intervention for the purpose of promoting stress relief, emotional regulation, and enhancing concentration in adolescents. Mostafazadeh et al (2019) reported that mindfulness training should be implemented in schools because they are effective in reducing depression, anxiety, and stress in high school students. Several other studies have reported that mindfulness programs are effective in lowering stress in children and adolescents ( Bluth et al, 2016 ; Kuyken et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, continuous mindfulness exercises lead to signi cant behavioral changes in self-care and dealing with confusion in nurses (21). MBCT interventions encourage individuals to practice frequently, focus attention on neutral stimuli and deliberate awareness of the body and mind, release mental preoccupation with threatening thoughts and worry about performance in the exam, and more e cient process of information, reducing physiological distress in the individual (22).…”
Section: Introductionmentioning
confidence: 99%